Community Assistance in Eradiating Tuberculosis in Pacalan Village, Magetan Regency - Hurip Jayadi; Sri Poerwati; Denok Indraswati; Lilis Prihastini; Hery Koesmantoro (Frontiers in Community Service and Empowerment, 2025)
Pulmonary Tuberculosis (Pulmonary TB) is an infectious disease that is still a health challenge in the community, especially in environments with inadequate sanitation. This community service program aims to improve community knowledge, attitudes, and skills in the prevention and eradication of pulmonary TB through education and environmental intervention in Pacalan Village, Plaosan District, Magetan Regency. The methods used include surveys of home conditions of pulmonary TB patients, health counseling, and physical interventions in the form of installing glass tiles to improve lighting and air circulation. This activity involved lecturers and students of the Sanitation Study Program of the Ministry of Health Surabaya, Magetan Campus and local health workers. The results of the activity showed an increase in public understanding of the symptoms, ways of transmission, and preventive measures for pulmonary TB. In addition, the intervention of installing glass tiles in the homes of people with Pulmonary TB has succeeded in improving the quality of ventilation and lighting, creating a healthier environment. In conclusion, an educational approach combined with physical intervention can increase public awareness and participation in the prevention of pulmonary TB. This program is expected to help reduce the incidence of pulmonary TB in the region and become a model for other regions with similar problems